35y2 + 12/y2 = 44

(iv) 35y2 + 12/y2 = 44



Sol. 35y2 + 12/y2 = 44



Multiplying throughout by y2 we get,



35y4 + 12 = 44y2



∴  35 (y2)2 – 44y2 + 12 = 0



 [ ∵ (am)n = am× n]



Substituting y2 = m we get,



35m2 – 44m + 12 = 0



∴ 35m2 – 14m – 30m + 12 = 0



 ∴ 7m (5m – 2) – 6 (5m – 2) = 0



 ∴ (5m – 2) (7m – 6) = 0



 ∴ 5m – 2 = 0 or 7m – 6 = 0



 ∴ 5m = 2 or 7m = 6



∴ m = 2/5  or m = 6/7



Resubstituting,  m = y2, we get;



∴ y2 =  2/5  or y2 = 6/7




∴  y = ±√(2/5)    or y = ±√(6/7)